Development of a Booklet on Organoleptic and pH Testing of Nata from Watermelon Rind as a Biotechnology Teaching Material for Grade XII Senior High School Students - Khansa Farahdilla Irfanindya Putri; Guntur Trimulyono; Firas Khaleyla (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2026)
Contextual teaching materials based on research findings can enhance students’ creative and innovative thinking skills, particularly in food biotechnology topics that also train students to analyze basic food quality and safety. However, the diversification of teaching materials remains limited. This study aims to develop a booklet on organoleptic and pH testing of nata from watermelon rind as a biotechnology teaching material for grade XII high school students, validated in terms of media, language, and content aspects. The development used the 4-D model (Define, Design, Develop, Disseminate), limited to the Develop stage (expert validation). Data were analyzed using a quantitative descriptive approach based on validations by expert lecturers and high school biology teachers. The results showed validity percentages of 98.61% for media, 94.10% for language, and 98.92% for content, with an overall average of 97.21% in the very valid category, indicating that the booklet is feasible for use as a teaching material. The primary content of the booklet supports Sustainable Development Goals (SDGs) 3 and 12 by employing watermelon rind waste and promoting responsible consumption and production practices.